2007
DOI: 10.2527/jas.2007-0056
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro reduction of sodium [36Cl]chlorate in bovine ruminal fluid1,2

Abstract: Sodium chlorate effectively reduces or eliminates gram-negative pathogenic bacteria in the gastrointestinal tracts of live cattle. Limitations to the in vivo efficacy of chlorate are its rapid absorption from the gastrointestinal tract and its presumed reduction to chloride within the gastrointestinal tract. We hypothesized that chlorate would be reduced via ruminal bacteria in a ruminal in vitro system and that the reduction of chlorate would be influenced by the dietary for-age:concentrate ratio; thus, 4 rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The methods 66 used by, and conclusions 59,60 of, Abdel Rahmen et al, who reported that chlorite is a stable residue in rats dosed with chlorine dioxide, chlorite, and chlorate have been refuted. 56 Instability of chlorite in biomatrices has been further demonstrated; for example 17.3 μg/mL of chlorite had a half-life of only 4.5 min in bovine ruminal fluid 67 and was a detectable, but transitory, metabolite of 36 Cl-chlorate in pure cultures of E. coli. 68 In the latter study, chlorite was only measurable by directly injecting culture fluid, without pretreatment, onto an ion chromatograph equipped with a radiochemical detector.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…The methods 66 used by, and conclusions 59,60 of, Abdel Rahmen et al, who reported that chlorite is a stable residue in rats dosed with chlorine dioxide, chlorite, and chlorate have been refuted. 56 Instability of chlorite in biomatrices has been further demonstrated; for example 17.3 μg/mL of chlorite had a half-life of only 4.5 min in bovine ruminal fluid 67 and was a detectable, but transitory, metabolite of 36 Cl-chlorate in pure cultures of E. coli. 68 In the latter study, chlorite was only measurable by directly injecting culture fluid, without pretreatment, onto an ion chromatograph equipped with a radiochemical detector.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Oliver et al (26) found that in vitro ruminal fluid cultures were capable of reducing moderate concentrations of chlorate (0.8 and 2.8 mM) during 24 h incubations. The degree of chlorate reduction (42% of total) for the 0.8 mM treatment of Oliver et al (26) was comparable to the degree of chlorate reduction (51%) for the 1 mM treatment of this study (Figure 2A,B).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, where chlorite was directly detected, only low quantities (23 ( 8 μM) of chlorite were present in pure culture at 12 h (Figure 3B), the time when chlorate reduction rates were maximal. Previously, we determined that the half-life of modest quantities (28 μM) of [ 36 Cl]chlorite under anaerobic culture conditions (live ruminal fluid) was about 4.5 min (26). In preliminary work for this study, we measured the stability of low concentrations (0.24 μM) of chlorite in TSB to ensure that, if formed, chlorite could be detected in our matrix; after 1 h in TSB, 86% of the starting chlorite remained (data not shown), indicating that the TSB itself would not quench the presence of chlorite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations